Breaking Down Barriers with the Usual Suspects: Findings from a Research-informed Intervention with Police, Young People and Residents in the West of Scotland. (April 2015) - Deuchar, Ross; Miller, Johanne; Barrow, Mark
This article draws upon international research evidence that suggests that cyclical stereotyping can emerge among young people, the police and local residents in communities. The article examines the impact of a research-informed local intervention in one of the most deprived communities in Scotland, where local perspectives were drawn upon as the basis for designing integration workshops. Pre- and post- interviews were conducted with young male participants, residents, police officers and youth workers. Findings suggest that the workshops stimulated social capital and fledgling attempts to generate collective efficacy. The authors draw upon the findings to make recommendations for policy, practice and research.